The detraining and retraining of an elite rower: a case study - Godfrey, R. J.; Ingham, S. A.; Pedlar, C. R.; Whyte, G. P. (Journal of Science and Medicine in Sport, 2005)
A heavyweight male rower, and current Olympic champion, undertook a laboratory-based incremental rowing test on four separate occasions; eight weeks prior to the Sydney Olympics (Pre OG), after eight weeks of inactivity (Post-IA), after 8 weeks of retraining (Post 8) and after a further 12 weeks of training (Post 20). Following the period of inactivity, peak oxygen uptake (VO2peak) declined by 8%, power at reference blood lactate concentrations declined by approximately 100 W (25%), and power at VO2peak was 20% lower. With eight weeks of retraining, rapid improvements were seen. For most parameters, however, the rate of improvement slowed and after 20 weeks of retraining the individual was approaching pre-Olympic levels. VO2 at lactate threshold as a percentage of VO2peak remained unchanged. These results show that detraining in the elite athlete can be pronounced, with rapid improvements upon retraining which slow, so that retraining takes considerably longer to achieve than detraining did. Complete cessation of training should be limited to short periods only in the preparation of the elite heavyweight rower. Any break should, if possible, include 'maintenance training'. In this way any decrements in those physiological parameters associated with 2000 m rowing performance will be minimised.